Neuropeptide Protocols - Irvine, G. Brent.; Irvine, G. Brent.; Williams, Carvell H.; Williams, Carvell H. (Methods in Molecular Biology,, 1997)
After 20 years of intensive effort, novel neuropeptides continue to be discovered, and the field of neuropeptide research is still expanding. As new analytical techniques become available, their applicability to the study of neu ropeptides brings fresh insights into the properties and functions of these ubiq uitous chemical messengers. Presented in this single volume, Neuropeptide Protocols, are 33 chapters covering these new techniques, together with more established methods. Each contributor is actively engaged in neuropeptide research and so brings to his or her description an awareness of the practical problems inher ent in the method, and provides sound advice on how to overcome them. The format conforms to the style of previous books in the Methods in Molecular Biology series. Each chapter provides an instruction to the technique, and item ized list of equipment and reagents, and a step-by-step set of instructions to enable practitioners to reproduce the method. The Notes section gives insights into pitfalls or critical stages, tips to overcome these obstacles, and sugges tions for extensions or modifications of the basic protocol. Neuropeptide Protocols is intended as a benchtop manual providing the entire gamut of techniques that form the essential tool kit of the practicing neuropeptide researcher. It will be useful for those new to the field, as well as for established workers who wish to try a new technique for the first time.